Inter‐breed diversity and temporal dynamics of the faecal microbiota in healthy horses. (16th September 2019) - Massacci, Francesca Romana; Clark, Allison; Ruet, Alice; Lansade, Léa; Costa, Marcio; Mach, Núria
Abstract: Understanding gut microbiota similarities and differences across breeds in horses has the potential to advance approaches aimed at personalized microbial modifications, particularly those involved in improving sport athletic performance. Here, we explore whether faecal microbiota composition based on faecal 16S ribosomal RNA gene sequencing varies across six different sport breeds at two time points 8 months apart within a cohort of 189 healthy horses cared for under similar conditions. Lusitano horses presented the smallest and Hanoverians the greatest bacterial diversity. We found subtle but significant differences in β‐diversity between Lusitano, Anglo Arabian and the central European breeds, and we reproduced these results across the two time points. Repeat sampling of subjects showed community to be temporally more stable in Lusitano and Anglo Arabian breeds. Additionally, we found that 27 genera significantly varied in abundance across breeds. Overall, 33% of these taxa overlapped with previously identified taxa that were associated with genetic variation in humans or other species. However, a non‐significant correlation was observed between microbial composition and the host pedigree‐based kinship. Despite a notable variation in the diversity and composition of the faecal microbiota, breed exerted limited effects on the equine faecal microbiota.